Determinant Factors of Financial Inclusion: Empirical Evidence in Indonesia using GMM - Dito Prakoso (Review on Islamic Accounting, 2022)
Financial inclusion is a process of involving people who do not have access to formal financial services. When a country is financially inclusive, economic activity in a country can depend on banking transactions and have greater financial sustainability and more effective monetary policy. The main objective of this research is to identify the factors that determine the level of financial inclusion in Indonesia and to suggest policy measures to increase the level of inclusion. This research uses the method Generalized Method of Moments (GMM) on 14 sharia banks full-fledge and Islamic bank units in Indonesia in the period 2010 to 2019. The results of this study found that bank size and deposit rates had a positive effect on the level of financial inclusion. Empirical findings also show that inflation has a negative and significant effect on financial inclusion.